Diet Beverage Intake and Risk of Chronic Kidney Disease in People with Type 2 Diabetes: An Individual Level Meta-Analysis. (29th May 2020) - Odegaard, Andrew; Jacobs, David; Steffen, Lyn; Rebholz, Casey; Tucker, Katherine; Mukamal, Kenneth; Pereira, Mark
Abstract: Objectives: Diet beverages are calorie free beverages sweetened with non-nutritive sweeteners. People with diabetes are the highest per-capita consumers of diet beverages, tending to consume them as a replacement for sugar sweetened beverages. This behavior is endorsed by dietetic and scientific organizations and diet beverages are marketed synonymously with better health. The underlying concern is the lack of data to support or refute this concept. To begin addressing this gap we examined the association between diet beverage intake and incident chronic kidney disease (CKD) in a population at high risk for CKD. Methods: We pooled data from the Atherosclerosis Risk in Communities study (years 1987–2014), Cardiovascular Health Study (1989–2014), Jackson Heart Study (2000–2012), and Multi-Ethnic Study of Atherosclerosis (2000–2013) to conduct a prospective study of the association of diet beverage intake with the incidence of CKD among participants with clinically ascertained type 2 diabetes (T2D) without prevalent CKD and with valid dietary data ( n  = 3250). CKD was defined using serum creatinine to define estimated glomerular filtration (eGFR) via the CKD-EPI creatinine equation. Incident CKD was defined as (eGFR <60 ml/min/1.73 m 2 ). We carried out a 2-step meta-analysis using individual level, cohort-specific regression analyses with identical adjustment for demographic, lifestyle, overall diet quality (Alternative Healthy Eating Index), energy intake, and clinical risk factors (baseline eGFR, total cholesterol, blood pressure, fasting glucose) to generate effect estimates that were pooled together using fixed and random effects meta-analysis. Results: 1018 participants developed CKD during follow-up. There was a positive association between diet beverage intake and risk of CKD. Compared to individuals reporting no intake of diet beverages, those consuming >0 and <1 diet beverage per day had a pooled relative risk and 95% confidence interval (RR, 95% CI) of 1.03 (0.87–1.22) and those consuming ≥1 beverage per day had a pooled RR (95% CI) of 1.20 (1.02–1.41). Conclusions: Diet beverage intake was associated with an increased risk of CKD in a diverse population with T2D. These results suggest the need to further examine the role of diet beverages in this high risk population. Funding Sources: AHA.